Driving contradictions: behaviors and attitudes regarding handheld and hands-free cellphone use while driving among young drivers - Lucas M. Neuroth; Dylan Galos; Li Li; Songzhu Zhao; Motao Zhu (BMC, 2021)
Abstract Background Cellphone use while driving (CUWD) is a frequent source of distraction for young drivers. These distractions commonly lead to motor vehicle crashes and, in some cases, death. Crash risk differs depending on if the driver is engaging in handheld or hands-free CUWD. This pilot study sought to investigate the differences between handheld versus hands-free CUWD behaviors in younger drivers and the attitudes and social norms that inform them. Methods Young drivers (mean age: 19.6 years, standard deviation: 0.8 years) were recruited from a large Midwestern city in the United States as part of a pilot study. The 62 enrolled drivers (51 females, 43 non-Hispanic white) completed an online survey measuring behavioral frequencies, attitudes, and social norms regarding talking on the phone, sending messages, and reading messages. These cross-sectional data were then categorized and used for a descriptive analysis. Results The majority of young drivers reported participating in some form of handheld CUWD, with reading messages being the most popular (95%). Only 43% of participants used hands-free technology for sending messages and 30% for reading messages, while half reported not using the technology at all. Whereas handheld messaging behaviors were viewed negatively by the participants, they were unsure of the impact on their driving ability and the legality surrounding hands-free messaging behaviors. Conclusions Handheld CUWD behaviors were more popular among young drivers compared to hands-free CUWD. Further, even though young drivers understood handheld cellphone use while driving is unsafe, they engaged in it anyway. The findings of this pilot study highlight the importance of better educational initiatives and optimizing hands-free interventions for young driver use cases.